Evaluating Evidence of Mechanisms in Medicine Principles and Procedures - Parkkinen, Veli-Pekka; Wallmann, Christian; Wilde, Michael; Clarke, Brendan; Illari, Phyllis; Kelly, Michael P.; Norell, Charles; Russo, Federica; Shaw, Beth; Williamson, Jon (SpringerBriefs in Philosophy,, 2018)
This book is open access under a CC BY license. This book is the first to develop explicit methods for evaluating evidence of mechanisms in the field of medicine. It explains why it can be important to make this evidence explicit, and describes how to take such evidence into account in the evidence appraisal process. In addition, it develops procedures for seeking evidence of mechanisms, for evaluating evidence of mechanisms, and for combining this evaluation with evidence of association in order to yield an overall assessment of effectiveness. Evidence-based medicine seeks to achieve improved health outcomes by making evidence explicit and by developing explicit methods for evaluating it. To date, evidence-based medicine has largely focused on evidence of association produced by clinical studies. As such, it has tended to overlook evidence of pathophysiological mechanisms and evidence of the mechanisms of action of interventions. The bookoffers a useful guide for all those whose work involves evaluating evidence in the health sciences, including those who need to determine the effectiveness of health interventions and those who need to ascertain the effects of environmental exposures.